A comparative study on reproductive performance and productivity of the Black Bengal and Crossbred goat at Atrai, Bangladesh (University Journal of Zoology, Rajshahi University, 2008)
The present investigation was carried out to detect the status of different productive and reproductive parameters of Black Bengal and Crossbred goats at Bandaikhara village under Atrai Upazilla of Naogaon district during the period of September to December/2005. The average age at first sign of heat of Black Bengal goats was better than that of Crossbred goats. In Black Bengal goat the average age at first kidding was 360.5±10 days, whereas, in crossbred goats it was 411.5±15.5 day. Significantly (P